Development and aging of superficial white matter myelin from young adulthood to old age: Mapping by vertex‐based surface statistics (VBSS). Issue 5 (9th March 2016) - Wu, Minjie; Kumar, Anand; Yang, Shaolin
Abstract: Superficial white matter (SWM) lies immediately beneath cortical gray matter and consists primarily of short association fibers. The characteristics of SWM and its development and aging were seldom examined in the literature and warrant further investigation. Magnetization transfer imaging is sensitive to myelin changes in the white matter. Using an innovative multimodal imaging analysis approach, vertex‐based surface statistics (VBSS), the current study vertexwise mapped age‐related changes of magnetization transfer ratio (MTR) in SWM from young adulthood to old age (30–85 years, N = 66). Results demonstrated regionally selective and temporally heterochronologic changes of SWM MTR with age, including (1) inverted U‐shaped trajectories of SWM MTR in the rostral middle frontal, medial temporal, and temporoparietal regions, suggesting continuing myelination and protracted maturation till age 40–50 years and accelerating demyelination at age 60 and beyond, (2) linear decline of SWM MTR in the middle and superior temporal, and pericalcarine areas, indicating early maturation and less acceleration in age‐related degeneration, and (3) no significant changes of SWM MTR in the primary motor, somatosensory and auditory regions, suggesting resistance to age‐related deterioration. We did not observe similar patterns of changes in cortical thickness in our sample, suggesting the observed SWM MTR changes are not due to cortical atrophy. Hum Brain Mapp 37:1759–1769, 2016 . ©2016 Wiley Periodicals, Inc.